Strategic continuous process improvement : which quality tools to use, and when to use them - Plenert, Gerhard Johannes (New York : McGraw-Hill, 2012)
'This practical guide explains how to implement a strategic performance model and select and integrate appropriate metrics to acheive desired goals.' -- from back cover.
Includes index.
Keywords: Total quality management; Quality control -- Standards